Nectin-4 in bladder cancer: biology and predictive biomarker potential. - Roessler, Navid; Miszczyk, Marcin; Berger, Walter; Englinger, Bernhard; Eckstein, Markus; Shariat, Shahrokh F. (Current Opinion in Urology, 2026)
PURPOSE OF REVIEW: This review aims to summarize the biology and clinical relevance of Nectin-4 in patients with advanced bladder cancer, with a focus on its role as a therapeutic target and predictive biomarker. RECENT FINDINGS: Nectin-4 is consistently overexpressed in advanced bladder cancer, facilitating tumor progression and survival signaling. Its cell surface localization makes it an ideal target for antibody-drug conjugates (ADCs), such as enfortumab vedotin, which has shown excellent efficacy in both first-line treatment, post platinum-based chemotherapy, and following immune checkpoint inhibitors. Recent insights highlight Nectin-4 as potential predictive biomarker and a target for advanced medical imaging strategies. Resistance mechanisms and new combination approaches are currently being investigated. SUMMARY: Nectin-4 is a key therapy target in patients with advanced bladder cancer, as demonstrated by the success of enfortumab vedotin. Emerging ADC technologies and Nectin-4-targeted imaging tools could improve efficacy and patient selection, redefining both diagnostic and therapeutic approaches.
EVALuna2:612962